Soybean Hypocotyls Prevent Calonectria ilicicola Invasion by Multi-Layered Defenses - Kobayashi, Michie; Win, Khin Thuzar; Jiang, Chang-Jie (Frontiers in Plant Science, 2022)
In plants, many pathogens infect a specific set of host organs to cause disease, yet the underlying mechanisms remain unclear. Here, we show that inoculation of soybean plants with Calonectria ilicicola, the soil-borne causal agent of soybean red crown rot, caused typical disease symptoms of root rot and leaf chlorosis and necrosis. However, the pathogen DNA was only detected in the roots and stem (hypocotyl) base but not other aerial parts of the plants. As we observed vigorous fungal growth in all culture media made of extracts from roots, stems, and leaves, differences in key components including available nutrients did not determine organ-specific infection and reproduction by C. ilicicola. Furthermore, inoculation of stems both with and without a surface wound showed that the stems resisted C. ilicicola infection via both the pre- and post-invasion defense layers. Transcriptomic comparison of roots and stems using RNA-seq analysis further revealed that upon C. ilicicola inoculation, a greater expression of genes involved in stress response was induced in the plant stems, including receptor-like kinase, AP2/ERF, MYB, and WRKY. In addition, pathways related to amino acid metabolism were also more upregulated in the stems in response to C. ilicicola infection. These results suggest that soybean stems provide C. ilicicola resistance, at least in part, by activating an organ-specific defense response.